Multilanguage Orthography for the Languages of Nepal - Regmi, Bhim Narayan (Gipan, 2017)
The earliest evidence of writing in Nepal is about 250 BC in Brahmi script and almost all the scripts used in present day Nepal—as many as fifteen—are the descendants of Brahmi which are built on the same formative principles of ’syllabic alphabet’. The existence of multilanguage orthographies as well as multiscripts has been the regular phenomenon in Nepal—independent to languages and language families. In the complexity of language-ethnicity and language-script relations, Nepali and the Devanagari script have been bearing the role of linking people in this country resulting from and resulted into a medium of education, media, and wider communication. Many scholars, following UNESCO 1951 report, have suggested for a standard orthography for the languages of Nepal, however, there are other views as well. In this background a Devanagari based multilanguage orthography have been proposed. This will fulfill the need of interoperable standard orthography in Nepal and benefit various types of users belonging to different language communities. The orthography will be shift from syllabic alphabet to alphabet as its systemic shift.